2017
DOI: 10.2169/internalmedicine.7629-16
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Emergency Department Visits and the Survival Rate for Colorectal Cancer Patients: A Nationwide Population-based Study

Abstract: Objective We examined the general characteristics, survival rate, and most common reasons for visiting the emergency department (ED) among colorectal cancer patients in Taiwan. We performed a population-based retrospective study and used data sourced from the National Health Insurance Research Database (NHIRD). Methods The colorectal cancer patient population, their diagnosis, and their medical management at the ED were identified using the Longitudinal Health Insurance Database 2000 (HV) codes and Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…As patients' disease burden changes over the course of living with, and dying from, cancer, their medication requirements will also change, both with regards to starting new medication for new symptoms, and stopping existing medication which may no longer be of benefit to them. Pain is the most commonly-reported symptom in patients who go on to die from cancer, and is a significant catalyst for unplanned escalations in care, particularly towards the end of life [10][11][12][13][14][15][16][17][18][19][20]. Most important priorities for people with life-limiting illness, such as advanced cancer, are centred around being comfortable and free from pain and maximising quality of life [6,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As patients' disease burden changes over the course of living with, and dying from, cancer, their medication requirements will also change, both with regards to starting new medication for new symptoms, and stopping existing medication which may no longer be of benefit to them. Pain is the most commonly-reported symptom in patients who go on to die from cancer, and is a significant catalyst for unplanned escalations in care, particularly towards the end of life [10][11][12][13][14][15][16][17][18][19][20]. Most important priorities for people with life-limiting illness, such as advanced cancer, are centred around being comfortable and free from pain and maximising quality of life [6,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Another observational study of 3347 colon cancer patients between 2000 and 2012 in Taiwan demonstrated that the number of visits increased steadily from 2000 to 2012 [ 17 ]. This increasing trend in ED visits was also observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients dying from cancer, the evidence was highly consistent across multiple publications in finding an association between gender (8 studies), age (5 studies), socioeconomic status (7 studies) and living arrangements (3 studies) and unscheduled care use among cancer decedents. Men were more likely to attend unscheduled care than women [6][7][8][9][10][11][12][13] . Older patients with cancer were more likely to use unscheduled care at the end of life than younger patients with cancer 6,7,9,13,14 .…”
Section: Demographymentioning
confidence: 97%
“…Cancer decedents who had lung cancer presented to unscheduled care more frequently than patients with other cancer types [7][8][9]12,14,16,20,21 . Pain was the single biggest clinical factor associated with use of unscheduled care, accounting for up to 83% of presentations 5,6,16,19,20,[22][23][24][25][26][27][28][29] . After pain, breathlessness 10,11,16,19,20,[22][23][24][25]27,29,30 , and gastrointestinal symptoms 10,16,19,20,[22][23][24][25][28][29][30] were consistently the most common reasons for visiting unscheduled care.…”
Section: Clinical and Patientmentioning
confidence: 99%
See 1 more Smart Citation